A path algorithm for robotic machining - Chin, Jih-Hua; Tsai, Her-Chyi (Robotics and computer-integrated manufacturing, 1993)
A path tracking algorithm for robotic continuous path machining is presented in this paper. The concept is to preadapt the path parameters before path tracking. The path concept itself arises from CNC machines so that a continuous path to be tracked/machined is built up from basic path types such as straight line, circular arc and parabola. Exact curve equations are used as tracking bases and a velocity correction which is created from the actual position error is added to the original desired path velocity. So a kind of cascaded path rate control and computed torque tracking is possible to produce a precise continuous path. An adaptive control is also proposed to support the path regulation with a tracking and an adaptation law. Simulation shows that the proposed algorithms yield better path precision than the pure computed torque method in three-dimensional path tracking/machining. And adaptive path regulation yields even better results.